Low-Power Upconversion in Anthracene Derivatives Doped with Pd(II) Tetraphenylporphyrin - Sun, Bin; Ye, Chang-Qing; Liang, Zuo-Qin; Ding, Ping; Wang, Xiao-Mei; Chen, Zhi-Gang; Tao, Xu-Tang; Wang, Qin-Hua (Asian Journal of Chemistry, 2014)
Selective low energy excitation of Pd(II) tetraphenylporphyrin in the presence of anthracene and anthracene-2-carboxylic acid, respectively, can yield easily visualized upconversion fluorescence at low excitation power. Anthracene-2-carboxylic acid shows about a two-fold increase in the upconversion quantum yield, relative to anthracene under the identical conditions. The higher fluorescence quantum of anthracene-2-carboxylic acid plays a crucial role in its effective upconversion fluorescence.